ANALISIS PERKEMBANGAN NPM, ROA DAN ROE PADA BANK SYARIAH INDONESIA SEBELUM DAN SESUDAH MERGER - Elsha Fitriyani; Lestari Oktavia; Sara Magdalena; Gunardi Gunardi; Priatna Kesumah; Rini Aisyah Yulianti (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2023)
In the midst of unstable economic conditions in various countries around the world, it requires every country to innovate and improvise in maintaining all aspects in order to survive. For this problem, one form of innovation carried out by the Indonesian government, especially in stock trading, is by merging syariah state-owned banks. The merger process of the three Islamic banks (BRI Syariah, BNI Syariah, and Mandiri Syariah) into an Bank Syariah Indonesia (BSI) with the BRIS code on the Indonesia Stock Exchange was carried out to expand BSI's market share. Therefore, the purpose of this study is to analyze the development profitability of BSM, BBRI, and BNIS before and after the merger into BSI. To support the research, the authors used a qualitative descriptive method with data obtained through secondary data from annual financial statements on the Indonesia Stock Exchange. The results showed that there was a development in profitability in each period at Bank Negara Indonesia Syariah (BNIS) and Bank Rakyat Indonesia Syariah (BRIS), while at Bank Syariah Mandiri (BSM) the analysis ROA and ROE values decreased from before and after the merger into Bank Syariah Indonesia (BSI).